2011
DOI: 10.1177/0954411911419061
|View full text |Cite
|
Sign up to set email alerts
|

The tribological behaviour of different clearance MOM hip joints with lubricants of physiological viscosities

Abstract: Clearance is one of the most influential parameters on the tribological performance of metal-on-metal (MOM) hip joints and its selection is a subject of considerable debate. The objective of this paper is to study the lubrication behaviour of different clearances for MOM hip joints within the range of human physiological and pathological fluid viscosities. The frictional torques developed by MOM hip joints with a 50 mm diameter were measured for both virgin surfaces and during a wear simulator test. Joints wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…This difference can be explained in part by the lower clearance (40µm less) of the Adept joints ( Table 4). The Adept clearance is high enough to overcome any fears around deformation during insertion [35] and high friction due to lubricant starvation [36], but low enough to reduce the volume lost as a result of the running in wear associated with higher clearance joints [17,37].…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be explained in part by the lower clearance (40µm less) of the Adept joints ( Table 4). The Adept clearance is high enough to overcome any fears around deformation during insertion [35] and high friction due to lubricant starvation [36], but low enough to reduce the volume lost as a result of the running in wear associated with higher clearance joints [17,37].…”
Section: Discussionmentioning
confidence: 99%
“…There are many different approaches to mimic the synovial fluid, most of them based on HA [25,28,35,38,39], carboxy methyl cellulose [40][41][42], polyvinylpyrrolidone [43] or polysaccharides (sodium alginate and gellan gum) [44,45] together a with single type of protein or with proteins from bovine serum. With these substances, the viscosity could be increased to values similar as in the synovial fluid [35,39,41,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The cohort of M2a-38mm™ components reviewed in this study showed no evidence of equatorial contact and the high wall thickness of the acetabular cups likely precluded this as a factor. Hu et al (22) also expressed concern about the lubricant starvation of low clearance bearings if the synovial fluid viscosity were higher than that of the 25% bovine serum used in simulator studies. While this could have been an issue, it is not present in the results for the NW group.…”
Section: Accepted Manuscript 4 Discussionmentioning
confidence: 99%